MIMICRY MARKETING STRATEGY (MMS) ON MARKETING PERFORMANCE: THE ROLE OF BUSINESS ENVIRONMENT AND TYPES OF INDUSTRY - Suliyanto Suliyanto; Ary Yunanto (TRIKONOMIKA, 2019)
Research about Mimicry Marketing Strategy (MMS) on marketing performance has been done before. However, in the previous study, there was no separation between the service industry and the manufacturing industry. In addition, there was also no experiment in the business environment with intense competition and business environment with non-intense competition. This study aims to analyze the effects of MMS on marketing performance in the service industry and manufacturing industry with intense and non-intense business environment. Respondents in this study were 100 MSMEs in Banyumas Regency, taken using Random Sampling method. The analytical tool used in this study is multiple regression analysis and regression analysis moderating sub-groups with a Chow-test. The results of this study indicate that mimicry towards consumers, mimicry towards competitors, and mimicry toward suppliers have positive effect on marketing performance, while mimicry on intermediaries does not have a positive effect on marketing performance, business environment and types of industry moderate the relationship between MMS and marketing performance.